BUDAYA MERANTAU MASYARAKAT NAGARI SUAYAN KECAMATAN AKABILURU KABUPATEN LIMA PULUH KOTA - meri yanti; afdhal afdhal (JURUSAN GEOGRAFI FIS UNP, 2020)
This study aims to identify, describe and analyze the driving and pulling factors of the Suayan community for marantau, as well as the positive and negative impacts of the marantau that exist in the Nagari Suayan community. This study uses qualitative research. The informants in this study were 10 people with key informants namely Mr. Afrizal AK.Tuo as the traditional leader of the village and the other nine additional informants, the selection of informants was carried out by purposive sampling. Data collection techniques used were observation, interviews, and documentation. Data analysis techniques used include; field notes, data reduction, data presentation, and conclusion drawing. The results of the study said that there were two driving factors, namely (a) The assumption of wandering had become a tradition and wandering to change fate. (b) Economic pressure. In addition there are several pull factors as well, namely (a) There is a promising job and income, (b) There is a gathering of fellow villagers. Positive impacts are (a) the economy is fulfilled, (b) getting prestige in the community. The negative impacts are, (a) the non-attendance of migrants, (b) often left by their husbands or sons to migrate.